Uji sitotoksisitas ekstrak sambiloto (andrographis paniculate ness) pada sel fibroblas dengan MTT - Sugandi Mastia Anugrah; Devi Rianti; Titien Hary Agustantina (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2019)
Sambiloto (Andographis Paniculata ness) is one of the plants that can be used as an alternative material of root canal irrigation. The phytochemical substance in the sambiloto extract such as flavonoids, tanin, alkaloid, saponin has been show to have antibacterial activity against Enterococcus faecalis. the ideal properties of an alternative material of root canal irrigants is not only have antibacterial activity but also is non-toxic to the tissues. Aim. The aims of this study is to determinate whether the sambiloto extract has cytotoxcic effect on human gingival fibroblast. The sambiloto extract was made by maceration method using ethanol 96% and certain dilution at 100% performed to obtain concentration 25 %, 12.5%, 6.25%, 3.125%, 1.56%, 2%, 1%, 0.50%, 0.25%. The cytotoxicity being tested on human gingival fibroblast by using MTT assay. The density of optic formazan indicated the number of living cell. Data were analyzed using one-way Anova test and Tukey HSD test with asignificance level of 0.05. The analysis data found significants differences in living cell percentation human gingival fibroblast after exposure of sambiloto extract with various concentration. Conclusions, Sambiloto extract at concentration of 25 % showed cytotoxcic effect toward human gingival fibroblast and at concentration 12.5%, 6.25%, 3.125%, 1.56%, 2%, 1%, 0.50%, 0.25% not showed cytotoxcic effect toward human gingival fibroblast.